Controller design based on Q-Parameterization method - Mohamad, Hussein Suleiman (2007)
This project presents the application of a robust controller design based on " Q-parameterization" theory (some time referred to as "Youla parameterization") for on a Magnetic suspension balance beam system. This controller is used in order to achieve both robust stability and good dynamic performance against the variation of system parameters. In the Q-parameterization method, the set of all stabilizing controllers of magnetic suspension balance beam system (MSBB) is characterized by a free parameter Q. This free parameter is chosen to using optimization technique to satisfy robust stability and other design requirements. The work was carried out in three stages. First, it starts with the derivation of the mathematical model of a magnetic suspension balance beam system (MSBB) in state space form. Second, the proposed Q-parameterization controller design methodology is presented. It should be noted that the degree of the resulting controller usually equals the degree of the plant plus the degree of the Q-parameter can be chosen to obtain a lower or higher order controller. Finally, the performance of the Q- parameterization controller in controlling the balance beam control system will be illustrated. For comparison purposes, the simulation of the pole placement and integral controllers were also carried out. Simulation results show the effectiveness of the proposed controller.